2021
DOI: 10.1002/advs.202005027
|View full text |Cite
|
Sign up to set email alerts
|

Control of Brain State Transitions with a Photoswitchable Muscarinic Agonist

Abstract: The ability to control neural activity is essential for research not only in basic neuroscience, as spatiotemporal control of activity is a fundamental experimental tool, but also in clinical neurology for therapeutic brain interventions. Transcranial-magnetic, ultrasound, and alternating/direct current (AC/DC) stimulation are some available means of spatiotemporal controlled neuromodulation. There is also light-mediated control, such as optogenetics, which has revolutionized neuroscience research, yet its cli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…The power dependence of the AUC yields an exponential factor of 3.1 (R 2 = 0.996), unambiguously confirming that PAI photoisomerization at 1560 nm follows a third-order non-linear process (3PE). The amplitude and fraction of responding cells display similar values but lower correlation, probably We have previously shown that PAI can control cardiac function in tadpoles and rats, [18d] and brain wave activity in mice [25] through the use of continuous wave illumination (1PE). Recently, we demonstrated in vivo photoswitching by 2PE in invertebrates.…”
Section: Resultsmentioning
confidence: 99%
“…The power dependence of the AUC yields an exponential factor of 3.1 (R 2 = 0.996), unambiguously confirming that PAI photoisomerization at 1560 nm follows a third-order non-linear process (3PE). The amplitude and fraction of responding cells display similar values but lower correlation, probably We have previously shown that PAI can control cardiac function in tadpoles and rats, [18d] and brain wave activity in mice [25] through the use of continuous wave illumination (1PE). Recently, we demonstrated in vivo photoswitching by 2PE in invertebrates.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that PAI can control cardiac function in tadpoles and rats, [18d] and brain wave activity in mice [25] through the use of continuous wave illumination (1PE). Recently, we demonstrated in vivo photoswitching by 2PE in invertebrates [18e] .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, introducing external interventions specifically aimed at manipulating adaptation mechanisms [23] and/or reinstating a correct excitation/inhibition balance [36] may further strengthen the link between the observed reduction of pathological sleep-like cortical dynamics and patients’ recovery of function. To date, evidence suggests that various tools including drug administration, opto-pharmacology, optogenetics, transcranial electrical stimulation, and repetitive TMS can modulate slow electrophysiological transients in simplified and in vivo experimental models [5860].…”
Section: Discussionmentioning
confidence: 99%